MATHEMATICAL METHOD OF DETERMINATION OF MULTIPLE FAILURES IN COMPLEX TECHNICAL SYSTEMS - Литвиненко, О. Є. (Proceedings of National Aviation University (archive), 2021)
The logical-linguistic model of determining multiple failures in complex technical systems is considered. The procedure for forming a system of algebraic equations, to solve which is described, is described the problem of diagnosing on the basis of the resulted model is reduced. An algorithm for solving the diagnostic problem, which implements a strategy of directed search of variants, is presented.